C++ Timesaving Techniques for Dummies - Telles, Matthew (Wiley Publishing, 2011)
Seasoned C++ programmer Matthew Telles shows developers at any level of experience how to save hours by improving, refactoring, and debugging their code Some of the techniques covered include mastering asserts, creating a complete class, hiding a method of a base class, freeing blocks of memory, implementing a simple locking mechanism, creating debugging macros, checking for errors at run-time, finding and fixing memory leaks, and reducing code complexity The easy-to-follow, two-column Timesaving Techniques format makes mastering each timesaver a snap C++ is one of today's most widely used programming languages, with compilers offered by Microsoft, Borland, and Code Warrior This book is the perfect companion to C++ For Dummies, Fifth Edition (0-7645-6852-3)